Constructive Dismissal dan Forced Resignation sebagai Celah Hukum Ketenagakerjaan - Andi Santri Syamsuri (Jurnal Hukum Lex Generalis, 2026)
This study critically examines the development of Indonesian labor law, particularly the two paradigms of termination: (constructive dismissal) (constructive layoffs) and (forced resignation) (forced resignation). Two main findings emerged from the data. First, the code of ethics (constructive dismissal) in the regulation reduces the value of severance compensation by 2 to 1 so as to eliminate the deterrent effect for employers. Second, there are some managers for employees to perform their practical obligations (forced resignation) through the scheme (forced resignation) through the scheme (quiet firing). The conclusion that the existing legislation creates an economic policy for companies to go along the path of least costly termination of employment, that is, the reform of the procedural law on payments and the creation of minimum Norms for the division of money.